Adenovirus Type 2 Early Nuclear and mRNA: Kinetic Estimation of l and r DNA Strand Fractions Complementary to Different Abundance Classes of Viral RNA - Wold, William S. M. (1977)
RNA from unfractionated cells, nuclei, and polyribosomes was extracted from adenovirus 2 (Ad2)-infected KB cells early in infection and annealed in vast excess in liquid to purified Ad2 l (heavy) and r (light) [(32)P]DNA strands (specific activity, 3 × 10(6) to 1.5 × 10(7) cpm/μg). The number of abundance classes of Ad2 RNA, their relative concentrations, and the strand fraction from which they arose were determined by a computer-assisted nonlinear regression analysis of hybridization kinetic data. Whole-cell RNA and nuclear RNA annealed to 60 and 40%, respectively, of l and r strands. Well-defined abundance (kinetic) classes were identified: abundant and scarce classes were complementary to 15 to 17 and 40 to 45%, respectively, of l strand, and to 11 to 16 and 17 to 23%, respectively, of r strand. In whole-cell RNA and nuclear RNA the abundant classes were 57 to 208 and 13 to 27 times more concentrated, respectively, than scarce classes. RNA-RNA hybrids were isolated that annealed to about 70% of both strands, indicating that whole-cell RNA and nuclear RNA hybridization values were minimal. Polyribosomal RNA appeared to anneal as three abundance classes to each DNA strand; abundant, scarce, and very scarce classes, respectively, hybridized to 6, 5, and about 10% of l strand and 7 (6 to 8), 10 (8 to 13), and about 19% of r strand. The abundant classes were 41 (11 to 67) times more concentrated than the scarce classes and 10(3) times more concentrated than the very scarce classes. Although the biological significance of these classes is not known, the very scarce classes probably represent nuclear RNA contaminants of polyribosomal RNA. The abundant and scarce classes may comprise mRNA, because together they are complementary to about the same fraction of each DNA strand (11% [10 to 12%] and 17% [14 to 20%] of l and r strands) known to be expressed as early mRNA. Thus, nuclear RNA contains Ad2 RNA sequences not found on polyribosomes; most or all of both DNA strands are transcribed, but only certain transcripts are processed into mRNA. It is not known whether “non-mRNA” transcripts are intermediates in the pathway of early mRNA production.